The Panarion of Epiphanius of Salamis, Book II and III : Book II and III (Sects 47-80, De Fide) - Salamis, Epiphanius of (Nag Hammadi and Manichaean Studies, 1993)
Epiphanius, bishop of Salamis on Cyprus from about 367 until 402, was a witness to and participant in the troubled era after the Council of Nicaea. His Panarion , or "Medicine Chest," is an historical encyclopedia of ideas and movements he considered heretical, and of the replies Christians ought to make to them. Book II and III deal with the Trinity, the Person of Christ, the divinity and personality of the Holy Spirit, Manichaeism, penance, matrimony and celibacy, monastic regulations, the Christian Calendar, all hotly contested topics in the fourth century. Book I, issued by Brill in 1987, concerns Gnosticism and Jewish Christianity. Together, the two volumes are the only complete translation of the Panarion in a modern language.